Overcoming Structural Barriers for Women in Entrepreneurship: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
While there has been growth in the number of women entrepreneurs in the United States in recent years, the percentage of women - particularly women of color - who decide to pursue an entrepreneurial career continues to be significantly lower than that of men. Entrepreneurship is a crucial enterprise responsible for driving innovation and economic growth, and increasing the representation of women, especially in STEM and medical (STEMM) industries, is critical to ensuring the nation's overall health, economic well-being, and global competitiveness. On June 21-22, 2021, the National Academies of Sciences, Engineering, and held a virtual workshop to explore the current structural barriers (i.e., policies, practices, or other norms that systematically perpetuate gender disparities) driving the underrepresentation of women entrepreneurs across STEMM industries and strategies to overcome these barriers. Participants included representatives from a variety of sectors, including higher education, government, nonprofits, and industry, as well as researchers, evaluators, inventors, mentors, consultants, and policy analysts, among others. This publication highlights the presentation and discussion of the workshop.
Keywords: Industry and Labor

Short-Term Strategies for Addressing the Impacts of the COVID-19 Pandemic on Women's Workforce Participation - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The COVID-19 pandemic and the associated recession have significantly affected women’s workforce participation. These impacts have varied from job loss to additional caregiving responsibilities. Black and Hispanic women have been particularly affected, bringing into sharp relief historical gender and racial inequities in the labor market. In order to address the impacts of the COVID-19 pandemic and resulting recession on women's employment, state and local decision makers can use available federal funds to mitigate those impacts while also laying the foundation for longer-term solutions. This rapid expert consultation identifies strategies that state and local decision makers can use to assist in short-term recovery efforts for women whose employment status and work experiences have been affected by the COVID-19 pandemic. It includes strategies both for supporting caregiving responsibilities and career development. This rapid expert consultation was produced through the Societal Experts Action Network (SEAN), an activity of the National Academies of Sciences, Engineering, and Medicine that is sponsored by the National Science Foundation and the Alfred P. Sloan Foundation. SEAN links researchers in the social, behavioral, and economic sciences with decision makers to respond to policy questions arising from the COVID-19 pandemic. This project is affiliated with the National Academies' Standing Committee on Emerging Infectious Diseases and 21st Century Health Threats. The white papers that informed the development of this rapid expert consultation were commissioned by the National Bureau of Economic Research with the support of the Alfred P. Sloan Foundation.
Keywords: Industry and Labor

Meeting Regional STEMM Workforce Needs in the Wake of COVID-19: Proceedings of a Virtual Workshop Series - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The COVID-19 pandemic is transforming the global economy and significantly shifting workforce demand, requiring quick, adaptive responses. The pandemic has revealed the vulnerabilities of many organizations and regional economies, and it has accelerated trends that could lead to significant improvements in productivity, performance, and resilience, which will enable organizations and regions to thrive in the "next normal." To explore how communities around the United States are addressing workforce issues laid bare by the COVID-19 pandemic and how they are taking advantage of local opportunities to expand their science, technology, engineering, mathematics, and medicine (STEMM) workforces to position them for success going forward, the Board of Higher Education and Workforce of the National Academies of Sciences, Engineering, and Medicine convened a series of workshops to identify immediate and near-term regional STEMM workforce needs in the wake of the COVID-19 pandemic. The workshop planning committee identified five U.S. cities and their associated metropolitan areas - Birmingham, Alabama; Boston, Massachusetts; Richmond, Virginia; Riverside, California; and Wichita, Kansas - to host workshops highlighting promising practices that communities can use to respond urgently and appropriately to their STEMM workforce needs. A sixth workshop discussed how the lessons learned during the five region-focused workshops could be applied in other communities to meet STEMM workforce needs. This proceedings of a virtual workshop series summarizes the presentations and discussions from the six public workshops that made up the virtual workshop series and highlights the key points raised during the presentations, moderated panel discussions and deliberations, and open discussions among the workshop participants.
Keywords: Industry and Labor

Diversity, Equity, and Inclusion in Chemistry and Chemical Engineering: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
A diverse workforce and inclusive workspaces are important components of future chemical and chemical engineering research. The workshop Diversity, Equity, and Inclusion in Chemistry and Chemical Engineering, held virtually on May 25-26, 2021, by the Chemical Sciences Roundtable, provided a venue for the chemical sciences community to discuss ideas and best practices for creating more diverse, equitable, and inclusive environments. Specifically, the workshop (1) explored barriers to diversity, equity, and inclusion (DEI) that are specific to chemistry and chemical engineering, (2) examined successful programs and best practices for increasing DEI in these fields, and (3) explored innovative approaches to create a culture in which all have equal opportunities to participate and advance. Ultimately, the workshop provided a forum for academic, government, and industrial participants to increase awareness of potential barriers to DEI and gain information needed to create more diverse, equitable, and inclusive environments in their workplaces. This document summarizes the presentations and discussions that took place during the workshop.
Keywords: Industry and Labor

Looking Ahead at the Cybersecurity Workforce at the Federal Aviation Administration - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The Federal Aviation Administration (FAA) has overseen significant upgrades to the technology used to manage aviation operations to increase the safety and efficiency of the National Airspace System (NAS). Though necessary to regular operations, these modern computing and communications systems provide a greater attack surface for criminals, terrorists, or nation-states to exploit and thereby increase the potential for cybersecurity threats to the NAS and its constituents. The future safety and security of air travel will rely in part on the ability of the FAA to build a workforce capable of addressing the evolving cybersecurity threat landscape. Securing the computers, networks, and data that underpin modern aviation depends in part on the FAA having enough cybersecurity professionals (capacity) with the right knowledge, skills, and abilities (capability)). It also depends on the FAA's workforce having sufficient diversity of backgrounds and experience. Such diversity is critical in analyzing cybersecurity problems and widely understood to be a "functional imperative" for effective cybersecurity programs. At the request of Congress, the publication examines the FAA's cybersecurity workforce challenges, reviews the current strategy for meeting those challenges, and recommends ways to strengthen the FAA's cybersecurity workforce.
Keywords: Industry and Labor; Computers and Information Technology

DoD Engagement with Its Manufacturing Innovation Institutes: Phase 2 Study Interim Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
To better support the need for timely, effective manufacturing technology development and transition, the Department of Defense (DoD) has established nine Manufacturing Innovation Institutes (MIIs) through its Defense-wide Manufacturing Science and Technology program element within the DoD Manufacturing Technology program. The Institutes are considered by DoD to be important facilitators that bring together innovative ecosystems in key technology and market sectors in the United States. The DoD MIIs are industry-led, with dual, public-private benefit, providing large commercial market potential while also meeting key U.S. defense industrial needs. The mission of the nine DoD-established Institutes addresses both defense and commercial manufacturing needs within specific, defense-relevant technology areas. The National Academies of Sciences, Engineering, and Medicine was asked to perform a follow-on study to its 2019 report Strategic Long-Term Participation by DoD in Its Manufacturing USA Institutes, which examined DoD's strategic relationship with the DoD Manufacturing Innovation Institutes. The Committee on DOD Engagement with Its Manufacturing USA MIIs Phase 2 Study was formed to provide strategic guidance in the following topics that were identified in the 2019 report for further exploration: protocols for conducting long term engagement assessments of the MIIs including evaluation metrics, best practices for MII education and workforce development programs, and development of strategies for better connecting MIIs to the broader DoD community. This interim report focuses on the protocol assessment topic in a timeframe that would allow its perspectives to be used in the execution of the first DoD 5-year MII evaluations planned for 2021.
Keywords: Industry and Labor; Conflict and Security Issues

Creating the Future Workforce in Food, Agriculture, and Natural Resources: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The production of food and other agricultural goods is a fundamental human endeavor and a cornerstone of the U.S. economy. While careers related to agriculture and natural resources have evolved in response to new knowledge and technology, consumer demands, and environmental changes, these professional fields now face a critical challenge: the ability to recruit and maintain a robust workforce. Companies, government bodies, and research organizations involved in food, agriculture, and natural resources (areas referred to collectively as FANR) are struggling to attract the next generation of workers. This shortage is apparent in employment projections for both trade positions attainable with certificate programs and high-tech positions requiring advanced degrees. Factors such as an increasingly diverse population, shifting work and career views, and lucrative job opportunities in other fields impact the ability to recruit talented individuals into the agricultural workforce. To provide a forum for discussing how the community might come together to address this challenge, the National Academies of Sciences, Engineering, and Medicine held a workshop on February 10-11, 2016, in Washington, DC. There were approximately 100 participants from land-grant universities, non-land-grant universities, minority-serving universities, community colleges, high schools, professional societies, government bodies, and corporations - reflecting the wide diversity of organizations with a stake in the future FANR workforce. The workshop was designed not only to highlight the significance of the challenges but also to surface concrete, forward-looking opportunities for action. This Proceedings of a Workshop summarizes plenary presentations from the workshop along with insights from 10 working groups that described key challenges, ongoing efforts to address them, and promising approaches for future action.
Keywords: Agriculture; Industry and Labor

DoD Engagement with Its Manufacturing Innovation Institutes: Phase 2 Study Final Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
To better support the need for timely, effective manufacturing technology development and transition, the Department of Defense (DoD) has established nine Manufacturing Innovation Institutes (MIIs) through its Defense-wide Manufacturing Science and Technology program element within the DoD Manufacturing Technology program. The institutes are considered by DoD to be important facilitators that bring together innovative ecosystems in key technology and market sectors in the United States. DoD MIIs are industry-led public private partnerships, with dual, public and private benefit, providing large commercial market potential while also meeting key U.S. defense industrial needs. The mission of the nine DoD-established institutes addresses both defense and commercial manufacturing needs within specific, defense-relevant technology areas. DoD Engagement with Its Manufacturing Innovation Institutes Phase 2 Study provides strategic guidance on protocols for conducting long term engagement assessments of the MIIs including evaluation metrics; best practices for MII education and workforce development programs; and development of strategies for better connecting MIIs to the broader DoD community and to other federal agencies. An interim report focused on the MII assessment protocol topic was published in April 2021 and is also included in this report, in appendixes C and D. This final report provides findings and recommendations relevant to education and workforce development best practices and DoD and other federal agency engagement strategies.
Keywords: Industry and Labor; Conflict and Security Issues